The relationship of Religiosity With Attitudes of Adolescents In Prevention of HIV/AIDS Infection - Ns. Syam’ani; Desty Natalia Damayanthi; Berthiana T (International Journal of Science, Technology & Management, 2021)
HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immuno Deficiency Syndrome) is one of the sexually transmitted diseases that attack the immune system of sufferers and can lead to death. This study uses the correlation with cross sectional approach. The sampling technique used in the study simple random sampling. Results:the results of the study showed respondents aged between 15-18 years old with 43 people sex men (53,1%), the female gender as much as 38 respondents (46.9%). The religiosity of young students the most in both categories as many as 53 respondents (65,4%) and attitude in the prevention of HIV/AIDS infection in the positive category as much as 64 respondents (79,0%). Based on the analysis provided by kendall's Tau (?) there is a meaningful relationship between religiosity and attitudes in the prevention of HIV infection/AIDS with the result p= 0.000 which means ? value <0.05. Based on these results it can be concluded there is a relationship between Religiosity with Attitudes of Adolescents In Prevention of HIV/AIDS Infection in Class XI SMAN 3 Palangka Raya.